Vascular Remodeling in Acute Respiratory Distress Syndrome: a Review - Cláudia Georgina de Quintal Matos (2020)
The Acute Respiratory Distress Syndrome (ARDS) promotes remodeling of the pulmonary vasculature. Since the first day of presentation, inflammation induces cytoskeletal remodeling of endothelial cells, alteration of cell junctions, adhesion molecules and glycocalyx, as well as dysregulation of signaling pathways. Vascular smooth muscle cells decrease their hypoxic pulmonary vasoconstriction (HPV) response, and might proliferate by similar mechanisms involved in pulmonary arterial hypertension (PAH) and hypoxia, increasing pulmonary vascular resistance (PVR) and pulmonary artery pressure (PAP). Tunica adventitia suffers collagen deposition by an intense extracellular matrix remodeling. Recovery of damaged vasculature depends on the degree of lesions. Endothelial progenitor cells and endothelial-to-mesenchymal transition might be important to repair pulmonary vasculature after ARDS resolution. No effective approved treatment exists against pulmonary vascular dysfunction during ARDS. Mesenchymal stem cell therapy appears to be a promisor alternative. However, more studies are needed to better understand vascular remodeling on ARDS, considering the effects of an unrecovered pulmonary vasculature and its sequels, like PAH.